2007
DOI: 10.1186/1471-2121-8-30
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hereditary hemochromatosis C282Y HFE protein in HEK293 cells activates specific endoplasmic reticulum stress responses

Abstract: BackgroundHereditary Hemochromatosis (HH) is a genetic disease associated with iron overload, in which individuals homozygous for the mutant C282Y HFE associated allele are at risk for the development of a range of disorders particularly liver disease. Conformational diseases are a class of disorders associated with the expression of misfolded protein. HFE C282Y is a mutant protein that does not fold correctly and consequently is retained in the Endoplasmic Reticulum (ER). In this context, we sought to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 70 publications
1
33
1
Order By: Relevance
“…Laboratory studies have identified the endoplasmic reticulum stress response as a potential shared pathway by which these two diseases could synergistically enhance cellular injury. 18 In this study, a novel A271S HFE mutation was also found in one a-1-antitrypsin deficiency case with heart failure and cardiac iron deposition. The systemic iron accumulation suggests that the mutation may have functioned in a similar manner to that of other HFE mutations in increasing iron deposition.…”
Section: Discussionmentioning
confidence: 85%
“…Laboratory studies have identified the endoplasmic reticulum stress response as a potential shared pathway by which these two diseases could synergistically enhance cellular injury. 18 In this study, a novel A271S HFE mutation was also found in one a-1-antitrypsin deficiency case with heart failure and cardiac iron deposition. The systemic iron accumulation suggests that the mutation may have functioned in a similar manner to that of other HFE mutations in increasing iron deposition.…”
Section: Discussionmentioning
confidence: 85%
“…In fact, at least seven missense mutations causing disease were reported at the HFE exon 4 (which codes for the α3 domain of the protein) including the major p.Cys282Tyr mutation, making this exon a hot spot for mutations. In the case of this mutation, the tyrosine for cysteine substitution disrupts the formation of the disulfide bond that physiologically occurs between Cys225 and Cys282 residues and that is essential for HFE association with β2-microglobulin [1,16,17]. Therefore, the p.Cys282Tyr-mutated HFE protein is unable to bind to the chaperone β2-microglobulin and to be transported to cell surface where it would interact with TfR1 and TfR2 in order to regulate hepcidin expression.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 The HFE C282Y mutation could contribute to this process either by accelerating or differentially activating UPR branches linked to tumor cell resistance. 48 Finally, we cannot completely rule out that other mechanisms, such as linkage disequilibrium with other genetic variants at risk on chromosome 6p, 49 were the HFE gene is located, might explain the association between C282Y heterozygosis, risk of ovarian cancer and survival.…”
Section: Discussionmentioning
confidence: 99%